Porosimetry: Porosimetry for Thin Films of Metal–Organic Frameworks: A Comparison of Positron Annihilation Lifetime Spectroscopy and Adsorption‐Based Methods (Adv. Mater. 17/2021). Issue 17 (27th April 2021) - Stassin, Timothée; Verbeke, Rhea; Cruz, Alexander John; Rodríguez‐Hermida, Sabina; Stassen, Ivo; Marreiros, João; Krishtab, Mikhail; Dickmann, Marcel; Egger, Werner; Vankelecom, Ivo F. J.; Furukawa, Shuhei; De Vos, Dirk; et al.
Abstract : Thin films of crystalline porous materials have great potential in membranes, sensors, and microelectronics. Still, characterizing their pore size, pore volume, and specific surface area is challenging. In article number 2006993, Rob Ameloot and co‐workers discuss positron annihilation lifetime spectroscopy, represented by the bees lighting up inside the honeycomb, in comparison to physisorption methods, symbolized by the quantification of honey in the pores.